Tying it All Together: Defining the Core Tenets of Funds of Knowledge. Issue 4 (4th July 2021) - Ramos, Delma; Kiyama, Judy Marquez
Abstract: Drawing on a synthesis of foundational and extant Funds of Knowledge (fk) scholarship that traces the framework's theoretical origins and development, this manuscript proposes a unified corpus of six core tenets for fk, as an extension to current theoretical understandings of the framework. These six core tenets are commonly cited individually within the fk research but not collectively considered, especially for their capacity to critically and conceptually shape research that engages the fk framework holistically and cohesively. To illustrate the proposed six core tenets of fk, authors present qualitative evidence from a transformative mixed methods study and an instrumental case study. Implications for designing a fk research agenda are provided.